Comparative Analysis Of Stock Performance Before And After Determining Asymmetric Auto Rejection In Companies Listed On The Idx - Sianturi, Friska Anarisma; Abdillah, Abdillah; Pauji, Ahmad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
ABSTRACTThe asymmetric auto rejection policy has an impact on stock performance, namely influencing investors' perceptions of the security and quality of order execution. Comparing stock performance before and after establishing asymmetric auto rejection can provide benefits for market players, namely evaluating effectiveness in improving market integrity and protecting investors. The aim of this research is to analyze the comparison of stock performance before and after the establishment of asymmetric auto rejection in companies listed on the IDX. The method used in this research is quantitative by collecting data in the form of historical stock data before and after the asymmetric auto rejection policy. The data analysis in this research used statistical tests with the help of SPSS version 26, namely paired t-test samples. The results of this research show that there is no significant difference between stock performance before the asymmetric auto rejection policy was implemented and stock performance after the asymmetric auto rejection policy was implemented. This is because the average value is only different by 0.033. Apart from that, the significance value is 0.975. This means that if it is greater than 0.05, H0 is accepted and H1 is rejected.